Bertani Diantara Himpitan Tambang (Belajar dari Petani Kutai Kartanegara) - M. Nazir Salim (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2016)
Abstract: Kutai Kartanegara (Kukar) is an area with quite extensive mining concession. However, Kukar is also the only district in East Kalimantan which experienced rice surplus. Although the amount of rice production is not significant, this condition should be appreciated, because in fact, the official releases shows its surplus is distinguish, compare to other district in East Kalimantan. Problems arise when massive mining operations occurred in those region. Some areas suffered real damage, especially agricultural land around the mining area. Damage is no longer a threat, but it has occurred and persisted. This study try to picture Kukar in the context of farming practices in the crush of mining Activities. There are three villages as observational study area, which are, Jembayan Dalam, Sedulang, and Sarinadi. The author's findings show that in the three villages, it is interesting to observe and to describe how exactly the problem of agricultural land degradation surrounding the mining existed, and how the community respond to this condition. Jembayan Dalam village and Sedulang suffer severe damages, even the land can no longer being used for farming. However, in Sarinadi, the author found interesting findings since as a farming village, its system and social structure which was built by the community is able to shield themselves from the onslaught of the mining financiers.Keywords: Kutai Kartanegara, agriculture land, mining Intisari: Kutai Kartanegara (Kukar) adalah sebuah wilayah dengan konsesi pertambangannya cukup luas, akan tetapi, Kukar juga satu-satunya kabupaten di Kalimantan Timur yang mengalami surplus beras. Walaupun tidak terlalu besar namun harus diapresiasi, karena faktanya, rilis angka-angka resmi pemerintah menunjukkan itu. Persoalannya, dengan masifnya operasi pertambangan, beberapa wilayah mengalami kerusakan yang cukup serius, khususnya lahan pertanian sekitar pertambangan. Kerusakan bukan lagi ancaman, namun sudah terjadi. Kajian ini akan mencoba melihat Kukar dalam konteks bertani dalam himpitan tambang. Ada tiga desa yang menjadi observasi kajian yakni Desa Jembayan Dalam, Sedulang, dan Sarinadi. Temuan penulis dalam tiga desa ini cukup menarik untuk melihat dan menggambarkan bagaimana sebenarnya persoalan kerusakan lahan pertanian sekitar pertambangan, baik problem maupun respons masyarakat. Desa Jembayan Dalam dan Sedulang mengalami kerusakan yang cukup parah, bahkan lahannya tidak bisa digunakan untuk bertani. Namun di luar itu, Sarinadi sebagai sebuah desa pertanian cukup menarik untuk dilihat karena sistem dan struktur sosial yang dibangun oleh masyarakat mampu membentengi diri dari serbuan para pemodal tambang.Kata Kunci: Kutai Kartanegara, lahan pertanian, pertambangan